Vetus testamentum, a quarterly published by the International Organization for the Study of the Old Testament, IOSOT (2013) - Joosten, Jan. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2015, ISBN: 9789004287389., 2013)
On the occasion of the twenty-first conference of the International Organization for the Study of the Old Testament, Brill and the editorial board of Vetus Testamentum present this publication of ten articles published in the journal between 1950 and today. Most of them have been seminal in one way or another, and all, we think, continue to repay close study. The selection was made so as to illustrate the diversity of subject matter, scholarly approach, and geographic provenance that characterizes Vetus Testamentum.